Integration of local and systemic immunity in ovarian cancer: Implications for immunotherapy - Rajtak, Alicja; Ostrowska-Leśko, Marta; Żak, Klaudia; Tarkowski, Rafał; Kotarski, Jan; Okła, Karolina (Frontiers in Immunology, 2022)
Cancer is a disease that induces many local and systemic changes in immunity. The difficult nature of ovarian cancer is the lack of characteristic symptoms which contributes to a delayed diagnosis and treatment. Despite the enormous progress in immunotherapy, its efficacy remains limited. The heterogeneity of tumors, lack of diagnostic biomarkers and complex immune landscape are the main challenges in the treatment of ovarian cancer. Integrative approaches which combine the tumor microenvironment – local immunity – together with periphery – systemic immunity – is urgently needed to improve the understanding of the disease and the efficacy of treatment. In fact, multiparametric analyses are poised to improve our understanding of ovarian tumor immunology. We outline an integrative approach including local and systemic immunity in ovarian cancer. Understanding the nature of both localized and systemic immune responses will be crucial to boosting the efficacy of immunotherapies in ovarian cancer patients.